The Role of Academic Supervision In Improving Teachers’ Professionalism at Mawaridussalam Islamic Boarding School - Maulana, Alpin Agus; Rahmawati, Wiki Tedi; Husna, Putri Lutfiah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the role of academic supervision in improving teachers’ professionalism at Mawaridussalam Islamic Boarding School. Academic supervision at Mawaridussalam Islamic Boarding School possesses distinct characteristics and is implemented systematically, differing significantly from public schools and several other Islamic boarding schools that have not yet adopted a similar system. The research method employed is descriptive qualitative with a case study design, involving several individuals as informants, including the Head of the Boarding School, the Head of the Education Department, the KMI (Kulliyatul Muallimin Al-Islamiyah) Division, and other related parties. Data collection techniques include in-depth interviews, direct observations, and document analysis related to the implementation of academic supervision. Based on the findings, academic supervision plays a significant role in enhancing teachers’ professionalism at Mawaridussalam Islamic Boarding School, particularly in teaching skills, pedagogy, discipline, and self-development. This serves as an innovative model to be applied in public schools and other Islamic boarding schools in an effort to improve the quality of education in Indonesia. Therefore, this research is expected to serve as a reference for developing more effective implementation of such programs in educational institutions and to provide insights for administrative staff in formal education institutions to improve teachers’ professionalism.